NEWS FROM CONGRESS OF AMERICAN HEART ASSOCIATION (NEW ORLEANS, NOVEMBER 2008): WHICH CONCLUSIONS WILL BE DONE FOR PRACTICAL MEDICINE - S. Y. Martsevich (Рациональная фармакотерапия в кардиологии, 2016)
.